Estudio de factibilidAS para la creación de una escuela de conducción no profesional en el cantón Montufar provincia del Carchi. - Velásquez Pantoja, Jennifer Patricia (2014)
In Ecuador and all around the world, a company in order to be created needs to be supported with a feasibility project that allows ease of decision making. Although this practice is unusual within the Carchi province because of the lack of knowledge about the process of preparing a feasibility project which permits to obtain actual data. This research seeks to promote the development of feasibility studies, studies that enables to evaluate the project and determine the viability of an investment. This in order to support investors to invest or not, giving them as backup information with data attached to reality. This work is established by chapters. It describes the problem of the current situation of driving schools in the country and within the province detailing the problem statement. Based on these aspects, a number of objectives to be achieved are proposed. Similarly, chapter one concerns the theoretical framework and basically it has relations with the variables and aspects that are investigated in driving schools. In chapter two describes the methodological framework that is going to be applied. Here is formulated the different aspects that were found which contribute to make investment decisions and to the approach of the proposal. This is presented as a summary in a graphical form. Finally, the chapter three details the practical framework that deals properly with the development of the proposal. Also it presents the main conclusions reached.